PENGARUH MODAL KERJA DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR BARANG KONSUMSI TERDAFTAR DI BEI PERIODE 2021-2024 - Ramatika; Nisfu Fhitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to examine the effect of working capital and profitability on firm value, both partially and simultaneously, in consumer goods sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research adopts a quantitative approach with a descriptive design. The data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results of the partial test (t-test) indicate that the Current Ratio (CR) has a negative and significant effect on firm value (Price to Book Value/PBV), with a significance value of 0.000 (< 0.05) and t-value exceeding the critical value in absolute terms (-2.594 > 2.00575). In contrast, Return on Assets (ROA) does not have a significant effect on PBV, as indicated by a significance value of 0.467 (> 0.05) and a t-value lower than the critical value (0.732 < 2.00575). Furthermore, the simultaneous test (F-test) shows that CR and ROA jointly have a significant effect on firm value, with a significance value of 0.000 (< 0.05) and an F-value greater than the critical value (3.792 > 3.17). The coefficient of determination (Adjusted R²) is 0.392, indicating that 39.2% of the variation in firm value can be explained by the independent variables, while the remaining 60.8% is influenced by other factors not included in this study. Keywords: Current Ratio (CR), Return on Assets (ROA), Price to Book Value (PBV)   Abstrak: Penelitian ini bertujuan untuk mengetahui apakah modal kerja dan profitabilitas secara parsial dan simultan berpengaruh terhadap nilai perusahaan pada perusahaan sektor barang konsumsi yang terdaftar di BEI periode 2021-2024. Jenis penelitian ini adalah penelitian kuantitatif yang bersifat deskriptif. Analisis data dalam penelitian ini menggunakan model analisis regresi linier berganda dengan menggunakan SPSS 27 for windows. Berdasarkan hasil uji t diketahui bahwa hasil CR nilai signifikansi sebesar 0,000 < 0,05 dengan -thitung < -ttabel (-2,594 > 2,00575), artinya CR berpengaruh negatif terhadap PBV. ROA menunjukkan nilai signifikansi sebesar 0,467 > 0,05 dan nilai thitung < ttabel (0,732 < 2,00575), artinya ROA tidak berpengaruh terhadap PBV. Berdasarkan hasil uji F menunjukkan bahwa secara bersama-sama variabel CR dan ROA mempunyai pengaruh terhadap PBV dengan nilai signifikansi 0,000 (0,000 < 0,05) dan dengan nilai Fhitung > Ftabel (3,792 > 3,17). Hasil uji koefisien determinasi (Uji-R2), nilai adjusted R square sebesar 0,392 atau 39,2%. Hal ini berarti bahwa 39,2% ROA bisa dijelaskan oleh variasi dari ketiga variabel independen (NPM, CR, DER). Kata Kunci: Modal Kerja, Profitabilitas dan Nilai Perusahaan